1998
DOI: 10.2466/pr0.1998.83.3f.1411
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Precognitive Dreams as Meaningful Coincidences

Abstract: 50 college students completed the Anomalous Experiences Inventory, the AT-20 measure of tolerance of ambiguity, and a frequency of dream recall questionnaire. Using path analysis we show that precognitive dreams can be modeled as accidental 'hits' with increased dream recall and the interpretation of such hits as 'meaningful coincidences' seems facilitated by a belief in the paranormal. As predicted, both factors are affected by tolerance of ambiguity, which provides the flexibility required to store and recal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
6
0
1
Order By: Relevance
“…We found 46.3% of participants had had at least one precognitive dream: Rattet and Bursik (2001) had found this for 44.8% of their sample, and Glicksohn (1990) for 22%. Number of precognitive dreams was positively associated with the degree of paranormal belief about these dreams (r ¼ 0.42), which accords with the correlation between these of r ¼ 0.48 found by Glicksohn (1990) and r ¼ 0.37 found by Houran and Lange (1998), and supports the view of Glicksohn, and also Blackmore and Tro s scianko (1985) and Ayeroff and Abelson (1976), that paranormal belief is related to personal experience. We found that higher education levels were related to lower paranormal belief, although this does not indicate the direction of causation.…”
Section: Discussionsupporting
confidence: 84%
“…We found 46.3% of participants had had at least one precognitive dream: Rattet and Bursik (2001) had found this for 44.8% of their sample, and Glicksohn (1990) for 22%. Number of precognitive dreams was positively associated with the degree of paranormal belief about these dreams (r ¼ 0.42), which accords with the correlation between these of r ¼ 0.48 found by Glicksohn (1990) and r ¼ 0.37 found by Houran and Lange (1998), and supports the view of Glicksohn, and also Blackmore and Tro s scianko (1985) and Ayeroff and Abelson (1976), that paranormal belief is related to personal experience. We found that higher education levels were related to lower paranormal belief, although this does not indicate the direction of causation.…”
Section: Discussionsupporting
confidence: 84%
“…To also assess phenomena of the esoteric scene, such as the belief in remedies of ''faithhealers'', ''the energy of stones'', ''astrology'' or ''palm-reading'' one extra scale with seven items was constructed (labelled ''Esotericism'') and one further item for the scale ''Superstition'' (''Broken glass brings luck'') in the hope of improving the reliability of the scale. The Poltergeist Experience Checklist (Houran & Lange, 1998) was also included in the study. Field dependence/independence was assessed with the EFT (Witkin et al, 1971) and for part of the sample also with the GWT (Hergovich & Ho¨rndler, 1994).…”
Section: Studymentioning
confidence: 99%
“…This may explain why paranormal believers often see coincidences as more meaningful (e.g. Brugger & Taylor, 2003;Houran & Lange, 1998). Further, it implies that paranormal believers base their probability judgements on what they perceive is typical of randomness and thus that they are especially prone to representativeness biases (Kahneman & Tversky, 1972;1983).…”
mentioning
confidence: 98%